Decision-Support Approaches for Sustainable Water Resource Management in Northwest Algeria - Baba, Alper; Meskine, Ahmed; Cherif, El Amine; Zerouali, Bilel; Ouadja, Abid; Santos, Celso Augusto Guimaraes; Bailek, Nadjem; Baba, Alper (Polish Society of Ecological Engineering – PTIE, 2025)
This study investigates water resource management in the Wilaya of Mostaganem, northwest Algeria, using the water evaluation and planning (WEAP) decision support tool in combination with the analytic hierarchy process (AHP). As water scarcity becomes increasingly critical due to population growth, agricultural demands, and climate variability, effective management strategies are essential. This research employs WEAP to simulate various water demand and supply scenarios, assessing the impacts of irrigation efficiency, industrial development, and climate conditions on water availability. Under the ASI scenario, unsatisfied water demand may reach 4.3 hm3 per year by 2027. However, improving irrigation efficiency could reduce this by up to 50% compared to the reference scenario. Seasonal variations reveal deficits reaching 3.2 hm3 per month during the summer months of July through October. Additionally, the study highlights that a significant increase in water demand, exceeding 80 hm3 by 2060, can be mitigated through improved water supply initiatives, such as constructing new dams. The integration of AHP enables the prioritization of management strategies based on stakeholder preferences, demonstrating that adapting to climate change can stabilize demand below 50 million cubic meters. This integrated approach provides valuable insights for policymakers and stakeholders in developing sustainable water resource strategies that address the challenges faced by the Mostaganem region.
Decision-Support Approaches for Sustainable Water Resource Management in Northwest Algeria
Santos, Celso Augusto Guimaraes/0000-0001-7927-9718; Ouadja, Abid/0000-0002-0547-5190; Bilel, Zerouali/0000-0003-4735-9750
Keywords: Water Resource Management; Analytical Hierarchy Process; Weap Model; Water Supply Strategies; Climate Variability; Agricultural Practices